PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DENGAN MEDIASI DISIPLIN KERJA (STUDI PADA GURU SMK NEGERI SUB RAYON 02 KOTA SEMARANG) - 11.52.02.0135, R.Ay.Hari Setyo Budi Santoso (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the effect of Work Motivation and The teachersâ Performance Competencies by Teachers Work Discipline mediation in SMK Negeri Semarang at Sub Rayon 2.The population in this study is 294 teachers, while the number of respondents is 100 samples and Civil Servants teacher of SMK Negeri SemarangatSubRayon2.The method of This research used descriptive method correlation. The collection data method use questionnaires with Likert scales in the range of 1 5, the data is used primary data or data obtained from respondents answers to questionnaire.Research results show that the effect on work motivation workplace discipline, teacher competence does not affect the work discipline, work motivation does not affect the performance of teachers, teachersâ competence was positively and significantly affect the performance of teachers, work discipline has significant positive effect on the teachersâ performance, work disciplne in influence on the performance of the teachersâ motivation , work discipline does not mediate the effect of job competence on teacher performance. Keywords: Work Motivation, Teacher Competence, Work Discipline and Teacher Performance